Development of Academic Programs in Human Resource Development in the United States. (November 2016) - Watkins, Karen E.; Marsick, Victoria J.
The Problem: As an applied academic field, human resource development (HRD) grew in response to the need for preparation of employees who were rotated into an HRD role with little or no academic preparation or training. Whatever their prior professional or generalist training, they found they were called on to develop others to improve performance. Professional associations initially filled this gap by offering training and certification, but over time, calls for formal preparation and credentialing led to the development of university-based programs. How did this process unfold for HRD over time? Where are academic programs in HRD now in their dual role—both preparing educators and supporting research to build a body of knowledge for this applied field? At what point does an occupation require an academic credential? The Solution: The birth of academic programs in HRD coincided with the burgeoning of the field of practice and its increasing pressure to establish itself as a profession with a unique set of competencies and a body of knowledge and skills. This article traces the history of academic programs in HRD and its progress toward professionalization. As practice has changed in depth and scope, it is helpful to ask whether academic curricula have deepened and broadened accordingly. What this means to HRD—what is included or excluded versus what might be more useful—is a question worth examining at this point in the history of these programs. The Stakeholders: Practitioners will find helpful information about distinctions among academic programs in HRD as well as about why it might be useful to obtain a degree in this field. HRD faculty will be able to locate their own programs within the broader academic field of HRD and better examine its unique focus against that of other HRD programs. Finally, scholars will be able to examine the role of practice and the press to professionalize and how this affects the evolution of an academic field.